Study of Low-temperature SiO2 Deposition and Carbon-doping using Remote Plasma Atomic Layer Deposition - 김홍기 (한양대학교, 2016)
Recently, high-quality SiO2 thin films deposited at low-temperature have been highlighted because of their excellent dielectric properties, such as high breakdown voltage, low leakage current, and low dielectric constant. In this study, silicon oxide thin films were deposited by means of remote plasma atomic layer deposition (RPALD) using a bis(tertiary-butylamino)silane (BTBAS), bis(trimethyl)silylmethane (BTMSM), and octamethyl(cyclotetra)siloxane (OMCTS) precursor and O2 plasma. In the case of RPALD using BTBAS, The growth rate was saturated at 1.0 Å/cycle between 300 °C and 400 °C and was consistent during the process. The SiO2 thin film was determined to be oxygen rich using Auger electron spectroscopy (AES), and the Si-O-Si bond structure was analyzed by measuring binding energy differences using X-ray photoelectron spectroscopy (XPS). The leakage current density was 2.0 × 10-7 A/cm2 at 2 MV/cm. As deposition temperature increased from 300 °C to 400°C, the breakdown voltage increased from 8.5 MV/cm to 10.5 MV/cm and the dielectric constant decreased from 3.85 to 3.72, which is slightly lower than typical SiO2. In the case of RPALD using BTMSM, SiOC thin film was deposited by modified ALD recipe due to low adsorptive reactivity. The growth rate of SiOC thin film is decease with increasing deposition temperature. The carbon contents was measured by AES, quantitatively and that is increase with decrease deposition temperature. The relative carbon composition (C/O+C) is decrease with increasing plasma power. In the case of RPALD using OMCTS, The growth rate was about 0.1 Å/cycle between 250 °C and 300 °C and was consistent during the process. The SiOC thin film was analyzed by XPS, and C 1s spectra shows the carbon contents in the thin film. C 1s peaks that indicate the carbon contents was diminished with increasing deposition temperature and pseudo SiO2 ¬was deposited at deposition temperature of 400 °C